2017
DOI: 10.14740/jocmr3049w
|View full text |Cite
|
Sign up to set email alerts
|

Oligoclonal Pattern/Abnormal Protein Bands in Post-Treatment Plasma Cell Myeloma Patients: Implications for Protein Electrophoresis and Serum Free Light Chain Assay Results

Abstract: BackgroundThe impact of autologous stem cell transplantation (ASCT) in plasma cell myeloma patients on the frequency, quality, and timing of oligoclonal pattern in serum protein electrophoresis/immunofixation electrophoresis (SPEP/SIFE) and serum free light chain assay (SFLCA) was evaluated.MethodsLaboratory results and clinical data for 251 patients with plasma cell myeloma, who had SPEP/SIFE and/or SFLCA performed between January 2010 and December 2016 were reviewed. The results for SPEP/SIFE and SFLCA were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 32 publications
(64 reference statements)
2
27
0
Order By: Relevance
“…Nevertheless recently, some other authors [14][15][16][17] have raised doubts about the real usefulness of sFLC, especially since the number of false positives and false negatives compared to serum protein electrophoresis (SPE) and sIFE are quite substantial. In the other hand, many factors can enhance those discrepancies such as renal failure [18], propensity of sFLC (especially those λ) to aggregate or polymerase, which may contributes to underestimation of λ FLC [15], hyper or hypogammaglobulinemia [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless recently, some other authors [14][15][16][17] have raised doubts about the real usefulness of sFLC, especially since the number of false positives and false negatives compared to serum protein electrophoresis (SPE) and sIFE are quite substantial. In the other hand, many factors can enhance those discrepancies such as renal failure [18], propensity of sFLC (especially those λ) to aggregate or polymerase, which may contributes to underestimation of λ FLC [15], hyper or hypogammaglobulinemia [19].…”
Section: Discussionmentioning
confidence: 99%
“…But the point still remaining is that sFLC measurement has the same utility and impact on MM diagnosis and monitoring. While some authors [16,17] reject the utility of sFLC in the monitoring of MM, because there is neither any benefit from sFLC ratio normalization in clinical remission in myeloma patients in terms of progression-free survival or overall survival [16], nor any significance of the presence of sFLC, especially in autologous stem cell transplantation (ASCT) where the apparition of oligoclonal pattern (which aren't synonymous to malignant monoclonal proteins), further degrades the performance of sFLC assay [17]. Recently some authors Michallet M & Greil C [20,21] reported that the use of serum Heavy/light chain is valuable as diagnosis and monitoring tool in MM patients, and that it correlates with clinical outcome in those patients.…”
Section: Discussionmentioning
confidence: 99%
“…SPEP was performed by agarose gel electrophoresis using Helena SPIFE 3000 system. Quantitative evaluation for the usual proteins and any M-proteins was performed by scanning the gel at 595 nm on an EDC densitometer [ 3 , 7 , 13 ]. If the monoclonal protein overlapped a normal protein band, the concentration of the combined peak was reported.…”
Section: Methodsmentioning
confidence: 99%
“…IgG kappa oligoclonal bands are the usual prominent “abnormal” bands and IgG kappa is also the most common immunoglobulin type of myelomas. Thus, for proper identification of stringent complete response and to avoid unnecessary treatment, it is imperative that we distinguish an oligoclonal band as not a residual or recurrent tumor, even though it is of the same immunoglobulin type as the initial malignant clone [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation